2014
DOI: 10.1021/ml500066m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Anilinopyrimidines as Dual Inhibitors of c-Met and VEGFR-2: Synthesis, SAR, and Cellular Activity

Abstract: Both c-Met and VEGFR-2 are important targets for cancer therapies. Here we report a series of potent dual c-Met and VEGFR-2 inhibitors bearing an anilinopyrimidine scaffold. Two novel synthetic protocols were employed for rapid analoguing of the designed molecules for structure-activity relationship (SAR) exploration. Some analogues displayed nanomolar potency against c-Met and VEGFR-2 at enzymatic level. Privileged compounds 3a, 3b, 3g, 3h, and 18a exhibited potent antiproliferative effect against c-Met addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…1‐((4‐Fluorophenyl)carbamoyl)cyclopropanecarboxylic acid (0.146 g, 0.654 mmol), HATU (0.415 g, 1.09 mmol), and DMF (5 mL) were placed in a round‐bottom flask, and then added DIPEA (0.26 mL, 1.49 mmol). Aniline 3 (0.157 g, 0.53 mmol) dissolved in DMF (5 mL) was added after 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…1‐((4‐Fluorophenyl)carbamoyl)cyclopropanecarboxylic acid (0.146 g, 0.654 mmol), HATU (0.415 g, 1.09 mmol), and DMF (5 mL) were placed in a round‐bottom flask, and then added DIPEA (0.26 mL, 1.49 mmol). Aniline 3 (0.157 g, 0.53 mmol) dissolved in DMF (5 mL) was added after 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The same trend is also seen with the trifluorinated compound 18d performing overall better in the cell‐based assay than compounds 14a and 15a , despite its lower c‐Met affinity. This observation is in compliance with known SAR on related structures that have shown that c‐Met affinity is more sensitive to modifications on the terminal benzene ring than is VEGFR . Compared with cabozantinib, higher growth suppressive effects are seen with 15b and 18b in several of the cell lines, particularly in cells derived from leukemia, CNS, and breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The combined basic extracts were then acidified to pH 1–2 with HCl (1 M), and the title compound was achieved by suction filtration as a white solid (0.41 g, 41%). 1 H NMR (400 MHz, DMSO‐ d 6 ): δ 10.71 (s, 1H), 7.60–7.57 (m, 2H), 7.15–7.10 (m, 2H), 1.39 (s, 4H) …”
Section: Methodsmentioning
confidence: 99%
“…The multitarget c-Met kinase inhibitor binds to the inactive conformation of the kinase and belongs to the type II c-Met kinase inhibitor 12,13 , which binds to not only c-Met but also VEGFR, FGFR, ALK, EGFR, MAT1R. All these studies suggest that simultaneous inhibition of the two tyrosine kinase receptors results in better anti-tumour effects 14,15 .…”
Section: Introductionmentioning
confidence: 99%